The Influence of Soft Skill and Hard Skill Development on Students Self-Efficacy and Work Readiness - Ismaya, Malika Indah Nur; Achmad, Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Introduction/Main Objectives: This paper discusses the work readiness of students at Universitas Muhammadiyah Surakarta. Background Problems: The study aims to determine the effect of soft skills, hard skills, and self-efficacy on students' work readiness. Novelty: Focusing specifically on students at Universitas Muhammadiyah Surakarta, this study analyzes the combined effect of soft skills and hard skills on self-efficacy and work readiness. Research Methods: Distributing questionnaires with respondent criteria, namely students of Muhammadiyah University of Surakarta class of 2021. Finding/Results: Soft skills and hard skills have a high correlation (r = 0.814), indicating that the two often develop together. Conclusion: Self-efficacy plays an important mediator between soft skills and hard skills on work readiness, with soft skills having a greater influence. The development of these three aspects is needed to improve students' work readiness.